Integrasi Pendidikan Anti Korupsi Dalam Kegiatan Osis Di Sma Negeri 2 Kota Tanjungpinang - Rilo Pambudi. S; Pery Rehendra Sucipta; Irwandi Syahputra (KARYA ABDI, 2021)
The number of corruption cases that occur in Indonesia is not sufficiently countered by repressive means. Preventive measures must also be synergized. The most appropriate effort is to instill anti-corruption values ​​in the younger generation, including high school students. The existence of the Student Council (OSIS) at SMA Negeri 2 Kota Tanjungpinang has an important role in grounding and implementing these values ​​in the school environment. This service was carried out by using the methods of lecturing, discussion, and brainstorming. The results show that the activity has succeeded in achieving its stated goals. This was evidenced by the enthusiasm and high response from the participants. In addition, OSIS SMA Negeri 2 Kota Tanjungpinang has been agreed to become an anti-corruption based OSIS. As astep first, the programs initiated in the discussion session were determined as part of the OSIS work program for SMA Negeri 2 Kota Tanjungpinang.